Functional outcome of fixation of distal femoral fractures with DF-LCP: a prospective study - T. P., Shafeed; Paul, Bijo (International Journal of Research in Orthopaedics, 2016)
Background: Management of supracondylar fractures is a real challenge to the orthopaedician due to its extensive soft tissue injury, boneloss, comminution, articular extention and instability. Open reduction and internal fixation with anatomical distal femoral locking plate permits early mobilization. Stable anatomical fixation is necessary to avoid complications and disability. Methods: 25 patients with Type A and Type C closed supracondylar femoral fractures were followed up from November 2013 to November 2015. All the patients underwent ORIF with DF-LCP. Clinical and radiological follow up were recorded for 24 months. Results: Mean time for fracture union was 4.02 months. Average duration for full weight bearing was 122 days (range 90-180days). The average range of movement for Type A fractures was 105.71 degrees, for C fractures average ROM was 93.64 degrees. Average ROM for patients <50 was 103 degree and for patients>50 ROM was 98.66 degree. Conclusions: Locked plating of DF fractures permits stable fixation and early mobilization which avoids disability and ensures good joint function.